White men's law: the roots of systemic racism - Irons, Peter H. (Oxford University Press, 2022)
"Thirty lashes, well laid on" -- "Dem was hard times, Sho' Nuff" -- "Beings Of an inferior order" -- "Fighting for white supremacy" -- "The foul odors of blacks" -- "Negroes plan to kill all whites" -- "Intimate contact with negro men" -- "I thanked got right there and then" -- "War against the constitution" -- "Two cities : one white, the other black" -- "All blacks are angry" -- "The basic minimal skills" -- Epilogue : "rooting out systemic racism".